2020
DOI: 10.1111/ans.16180
|View full text |Cite
|
Sign up to set email alerts
|

Does well‐controlled overt hypothyroidism increase the risk of total knee arthroplasty?

Abstract: Background: Overt hypothyroidism is widely accepted as a risk factor for adverse events following total knee arthroplasty (TKA). However, no prior study has preoperatively reversed hypothyroidism and reevaluated its risk. This retrospective study aimed at investigating whether well-controlled overt hypothyroidism would still increase the risk of TKA. Methods: Between November 2009 and November 2016, patients diagnosed with overt hypothyroidism but well controlled and underwent TKA were compared with euthyroid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(17 citation statements)
references
References 26 publications
0
17
0
Order By: Relevance
“…All studies reporting perioperative blood loss-related complications demonstrated a significantly higher rate of postoperative anemia in hypothyroid than euthyroid patients undergoing TJA ( 7 , 14 , 16 , 17 ). These studies also showed a significant increase in transfusion rates in patients with hypothyroidism, except for the study by Yuan et al .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…All studies reporting perioperative blood loss-related complications demonstrated a significantly higher rate of postoperative anemia in hypothyroid than euthyroid patients undergoing TJA ( 7 , 14 , 16 , 17 ). These studies also showed a significant increase in transfusion rates in patients with hypothyroidism, except for the study by Yuan et al .…”
Section: Resultsmentioning
confidence: 99%
“…They mainly were retrospective and prospective observational and cohort studies. One study presented data on total ankle arthroplasty ( 13 ); four studies presented data on TKA ( 7 , 14 , 15 , 16 ); one study included data on THA ( 17 ); and one for total elbow arthroplasty ( 18 ). Two studies demonstrated data on both TKA and THA operations ( 19 , 20 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations